Implementasi Penguatan Pendidikan Karakter Religius Melalui Program Wirid Remaja - Putra, Rido; Nopriza, Cici (An-Nuha, 2025)
This research is motivated by the importance of developing students' character amidst the challenges of the times, as well as the need for a deeper understanding of the implementation of the youth wirid program as part of efforts to strengthen religious character education. This research aims to determine how to plan, implement and evaluate the program to enhance religious character education through youth wirid activities at SMA Negeri 2 Lengayang, Pesisir Selatan Regency. The research method used is descriptive qualitative. The results of the research show that teenage wirid activities, which include congregational midday prayers, religious lectures, tahfidz Al-Qur'an, infaq, and attendance, effectively foster religious values ​​such as discipline, responsibility, tolerance, and love for Islamic teachings. Evaluations carried out regularly help encourage the improvement and development of activities. The youth wirid program makes a significant contribution in shaping students' religious character.